2021
DOI: 10.2147/jir.s318812
|View full text |Cite|
|
Sign up to set email alerts
|

Gamma Radiation Induce Inflammasome Signaling and Pyroptosis in Microvascular Endothelial Cells

Abstract: Introduction:The extend to the clinical benefit of radiation therapy is the inability to eliminate only cancer cells and destroy normal cells such as microvascular endothelial in the vascular niche and turn induced-inflammasome signaling and cell death. These unfortunate injuries generated by ionizing radiation alter the therapeutic window and result in the reoccurrence of the malignancy. Therefore, we engaged in vitro studies by demonstrating radiation-induced inflammasome and cell death in endothelial cells.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…However, there is a lack of study on its role in radiation-induced intestinal injury. Although some studies had suggested the involvement of pyroptosis in radiation damage of cells [10,11], the properties speci c to radiation is not highlighted and the role of GSDMD is not clear. To ll this gap, we respectively explored the in vivo effect of GSDMD knock-out on the survival and intestinal function in mice, and its in vitro effect on radiation sensitivity of intestinal epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is a lack of study on its role in radiation-induced intestinal injury. Although some studies had suggested the involvement of pyroptosis in radiation damage of cells [10,11], the properties speci c to radiation is not highlighted and the role of GSDMD is not clear. To ll this gap, we respectively explored the in vivo effect of GSDMD knock-out on the survival and intestinal function in mice, and its in vitro effect on radiation sensitivity of intestinal epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Current studies have revealed the association between pyroptosis and radiation-induced injury, yet the speci c function of GSDMD remains elusive [10,11]. In the present study, we established GSDMD knockout mouse to deeply research into the role of GSDMD and pyroptosis in RIII.…”
Section: Introductionmentioning
confidence: 92%
“…Moreover, the epithelial tissues, such as oral mucosa, gut mucosa, as well as lung epithelium, are particularly susceptible to ionizing radiation. Inflammasome activation and pyroptosis have been observed in these tissues after exposure to radiation ( 47 , 48 , 53 , 69 ). Excessive cell death in epithelium may lead to the breakdown of barriers such as skin, gut mucosal barrier, and alveolar epithelial barrier.…”
Section: Damage Caused By Radiation-induced Inflammasomementioning
confidence: 99%
“…LPS from Gram-negative bacteria may also contribute to the inflammasome cascade through non-canonical NLRP3 inflammasome activation, thereby leading to even deteriorated conditions ( 29 ). Equally important, immoderate cell death in vascular endothelial cells causes vascular dysfunction, leading to increased permeability, impaired vascular tone, and altered blood homeostasis, aggravating already severe damage caused by radiation ( 10 , 53 ).…”
Section: Damage Caused By Radiation-induced Inflammasomementioning
confidence: 99%
“…The small molecule inhibitor of Mammalian apurinic/apyrimidinic (AP) endonuclease 1(APE1) can induce pyroptosis in NSCLC cells [10]. APE1, also known as APEX1, is a multifunctional enzyme involved in the BER pathway and in transcriptional regulation [11].…”
Section: Introductionmentioning
confidence: 99%